Sustaining Rare Marine Microorganisms: Macroorganisms As Repositories and Dispersal Agents of Microbial Diversity - Troussellier, Marc; Escalas, Arthur; Bouvier, Thierry; Mouillot, David (Frontiers in Microbiology, 2017)
Recent analyses revealed that most of the biodiversity observed in marine microbial communities is represented by organisms with low abundance but, nonetheless essential for ecosystem dynamics and processes across both temporal and spatial scales. Surprisingly, few studies have considered the effect of macroorganism-microbe interactions on the ecology and distribution dynamics of rare microbial taxa. In this review, we synthesize several lines of evidence that these relationships cannot be neglected any longer. First, we provide empirical support that the microbiome of macroorganisms represents a significant part of marine bacterial biodiversity and that host-microbe interactions benefit to certain microbial populations which are part of the rare biosphere (i.e. opportunistic copiotrophic organisms). Second, we reveal the major role that macroorganisms may have on the dispersal and the geographic distribution of microbes. Third, we introduce an innovative and integrated view of the interactions between microbes and macroorganisms, namely sustaining the rares, which suggests that macroorganisms favor the maintenance of marine microbial diversity and are involved in the regulation of its richness and dynamics. Finally, we show how this hypothesis complements existing theories in microbial ecology and offers new perspectives about the importance of macroorganisms for the microbial biosphere, particularly the rare members.